Morinda citrifolia noni water extract enhances innate and adaptive immune responses in healthy mice, ex vivo, and in vitro. (10th January 2019) - Hong, Yo Han; Yi, Young‐Su; Han, Sang Yun; Aziz, Nur; Kim, Han Gyung; Park, Sang Hee; Hossain, Mohammad Amjad; Baik, Kwang Soo; Choi, Su Young; Lee, Jongsung; Kim, Jong‐Hoon; Cho, Jae Youl
Abstract : Although Morinda citrifolia (noni) has long been used in traditional medicines for human diseases, its molecular and cellular mechanism of immunostimulatory ability to improve human health under normal healthy conditions is not fully elucidated. This study aimed to investigate the in vitro and in vivo immunostimulatory activity of M. citrifolia fruit water extract treated with enzymes (Mc‐eWE). In vitro studies revealed that Mc‐eWE stimulated the cells by inducing nitric oxide (NO) production and the expression of inflammatory cytokines, such as interleukin (IL)‐1β, IL‐6, IL‐12, tumor necrosis factor‐alpha (TNF‐α), and interferon‐gamma (IFN‐γ). The immunostimulatory activity was mediated by activation of NF‐κB and AP‐1. Ex vivo studies showed that Mc‐eWE stimulated splenocytes isolated from mice by inducing NO production and expression of immunostimulatory cytokines and by downregulating the expression of the immunosuppressive cytokine IL‐10 without cytotoxicity. In vivo demonstrated that Mc‐eWE induced immunostimulation by modulating populations of splenic immune cells, especially by increasing the population of IFN‐γ + NK cells. Mc‐eWE enhanced the expression of inflammatory genes and immunostimulatory cytokines and inhibited the expression of IL‐10 in the mouse splenocytes and sera. Taken together, these results suggest that Mc‐eWE plays an immunostimulatory role by activating innate and adaptive immune responses.